2015
DOI: 10.2463/mrms.2014-0120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracranial Dural Arteriovenous Fistulas: Comparison of Unenhanced 3T 3D Time-of-flight MR Angiography with Digital Subtraction Angiography

Abstract: Purpose: We compared gross characterization of intracranial dural arteriovenous fistulas (DAVFs) between unenhanced 3-tesla 3-dimensional (3D) time-of-flight (TOF) magnetic resonance angiography (MRA) and digital subtraction angiography (DSA).Methods: We subjected 26 consecutive patients with intracranial DAVF to unenhanced 3T 3D TOF MRA and to DSA. Two independent sets of observers inspected the main arterial feeders, fistula site, and venous drainage pattern on MRA and DSA images. Interobserver and intermoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Time-of-flight (TOF)-MRA has been the most widely used of these in clinical practice. Past studies have identified TOF-MRA as a sensitive tool for detecting AVS without contrast material [23][24][25][26][27][28]. Even with parallel imaging (PI), a widely used method for k-space undersampling, TOF-MRA requires a long scanning time, since both wide scan coverage and high resolution are required in the assessment of AVS due to its complex angioarchitecture and hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Time-of-flight (TOF)-MRA has been the most widely used of these in clinical practice. Past studies have identified TOF-MRA as a sensitive tool for detecting AVS without contrast material [23][24][25][26][27][28]. Even with parallel imaging (PI), a widely used method for k-space undersampling, TOF-MRA requires a long scanning time, since both wide scan coverage and high resolution are required in the assessment of AVS due to its complex angioarchitecture and hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…TOF angiography at clinical field strengths is applied in the brain mainly to detect neurovascular diseases such as intracranial stenosis or unruptured aneurysms . Although the noninvasive diagnosis of small vessels, such as arteriovenous malformations, dural arteriovenous fistulas, and detection of arterial feeders of intracranial tumors, is possible with TOF, digital subtraction angiography (DSA) has been shown to yield superior sensitivity and specificity due to higher spatial resolution and image quality . Thus, DSA remains the gold standard imaging modality for small cranial arteries, regardless of its related radiation exposure for staff and patients; low but significant risks of neurological deficit; complications; or idiosyncratic reactions due to artery puncture, catheter placement, and iodinated contrast agent .…”
Section: Introductionmentioning
confidence: 99%
“…DSA-imaging was evaluated by a third radiologist. A diagnostic confidence score was used for the presence of abnormalities associated with AV-shunting (15). AVMs were characterized using the Spetzler-Martin-scale, AVFs were characterized using the Borden classification.…”
mentioning
confidence: 99%